2004
DOI: 10.1021/nl048969z
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing Single-Walled Carbon Nanotubes with Surfactants:  A Small Angle Neutron Scattering Study

Abstract: We have investigated the dispersion of single-walled carbon nanotubes (SWNTs) in heavy water with the surfactant octyl-phenol-ethoxylate (Triton X-100) using small angle neutron scattering. The results indicate an optimal surfactant concentration for dispersion, which we suggest results from competition between maximization of surfactant adsorption onto SWNT surfaces and a depletion interaction between SWNT bundles mediated by surfactant micelles. The latter effect drives SWNT reaggregation above a critical vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
266
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(276 citation statements)
references
References 34 publications
10
266
0
Order By: Relevance
“…The diameter curves for the dispersed P-SWCNTs overlapped with each other, regardless of the amount of SDBS (Figure 2(a)) or P-SWCNTs (Figure 3(a)) added, indicating that the degree of dispersion of the P-SWCNTs was independent of the amount of surfactant or CNTs added. This was consistent with the observations made by Clark et al [39] and Wang et al [40], which showed that the particle size was not sensitive to surfactant concentration, especially at high surfactant and SWCNT concentrations.…”
Section: The Role Of Sonication Time Output Power and Optimal Energsupporting
confidence: 93%
“…The diameter curves for the dispersed P-SWCNTs overlapped with each other, regardless of the amount of SDBS (Figure 2(a)) or P-SWCNTs (Figure 3(a)) added, indicating that the degree of dispersion of the P-SWCNTs was independent of the amount of surfactant or CNTs added. This was consistent with the observations made by Clark et al [39] and Wang et al [40], which showed that the particle size was not sensitive to surfactant concentration, especially at high surfactant and SWCNT concentrations.…”
Section: The Role Of Sonication Time Output Power and Optimal Energsupporting
confidence: 93%
“…Using simulation in physics allows the number of experiments to be reduced and thus time and cost for development at laboratory and industry scale by linking theory and experimentation [10][11][12][13][14][15][16]. Functionalisation of nanoparticles, when they are dispersed in an epoxy resin, could have two aims: improving the dispersion quality by decreasing the interaction between nanoparticles [17][18][19], and improving the mechanical properties of the composite by improving the interfacial bonding between matrix, nanoparticles and micro-reinforcement [20][21][22][23]. When nanoparticles are dispersed in an epoxy resin, they have a tendency to re-agglomerate and create only weak bonds with the epoxy molecules by Van der Waals interaction.…”
Section: Fabrication Challengesmentioning
confidence: 99%
“…sodium dodecyl sulphate (SDS) [18], sodium dodecyl benzenesulfonate (NaDDBS) [41,42]; and (ii) non-ionic e.g. Triton X-100 [17,19].…”
Section: Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotubes have been dispersed and stabilised with the aid of specific solvents [16][17][18][19][20][21][22][23][24] , acids [25,26] , macromolecules [27][28][29][30] and surfactants [31][32][33][34] as well as through covalent functionalisation strategies [35,36] . Such systems have been characterised by a range of techniques such as atomic force microscopy [37] , infra-red photoluminescence and absorbance spectroscopy [34] , viscometry [25] , small angle neutron scattering [32] to name but a few. These strategies have been extremely successful, resulting in highly exfoliated, well defined and comprehensively characterised systems of dispersed nanotubes.…”
Section: Introductionmentioning
confidence: 99%